Interleukin-10 contrasts inflammatory synaptopathy and central neurodegenerative damage in multiple sclerosis - Gilio, Luana; Fresegna, Diego; Stampanoni Bassi, Mario; Musella, Alessandra; De Vito, Francesca; Balletta, Sara; Sanna, Krizia; Caioli, Silvia; Pavone, Luigi; Galifi, Giovanni; Simonelli, Ilaria; Guadalupi, Livia; et al. (Frontiers in Molecular Neuroscience, 2024)
Proinflammatory cytokines are implicated in promoting neurodegeneration in multiple sclerosis (MS) by affecting excitatory and inhibitory transmission at central synapses. Conversely, the synaptic effects of anti-inflammatory molecules remain underexplored, despite their potential neuroprotective properties and their presence in the cerebrospinal fluid (CSF) of patients. In a study involving 184 newly diagnosed relapsing–remitting (RR)-MS patients, we investigated whether CSF levels of the anti-inflammatory interleukin (IL)-10 were linked to disease severity and neurodegeneration measures. Additionally, we examined IL-10 impact on synaptic transmission in striatal medium spiny neurons and its role in counteracting inflammatory synaptopathy induced by IL-1β in female C57BL/6 mice with experimental autoimmune encephalomyelitis (EAE). Our findings revealed a significant positive correlation between IL-10 CSF levels and changes in EDSS (Expanded Disability Status Scale) scores one year after MS diagnosis. Moreover, IL-10 levels in the CSF were positively correlated with volumes of specific subcortical brain structures, such as the nucleus caudate. In both MS patients’ CSF and EAE mice striatum, IL-10 and IL-1β expressions were upregulated, suggesting possible antagonistic effects of these cytokines. Notably, IL-10 exhibited the ability to decrease glutamate transmission, increase GABA transmission in the striatum, and reverse IL-1β-induced abnormal synaptic transmission in EAE. In conclusion, our data suggest that IL-10 exerts direct neuroprotective effects in MS patients by modulating both excitatory and inhibitory transmission and attenuating IL-1β-induced inflammatory synaptopathy. These findings underscore the potential therapeutic significance of IL-10 in mitigating neurodegeneration in MS.